Learning From Failure in an Organization Designed to Develop Success. (December 2020) - Bartunek, Jean M.
In this article, I discuss events associated with leadership and fiscal crises that occurred at NTL during the late 1960s and early 1970s, after Warren Bennis declined to accept the Director position and until a group of NTL members led by Edith Seashore "rescued" NTL in 1975. In particular, I consider Warner Burke's experience in the midst of these events. This episode in the history of NTL enables us to reflect on important questions about relationships between the theory and practice of Organization Development and learning from organizational failure.